ANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF IMATINIB MESYLATE AND ITS DIMER IMPURITY IN PHARMACEUTICAL FORMULATION BY REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - Kuna, Arun Kumar; Seru, Ganapaty; Radha, Gadela Venkata (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study is to develop a simple, specific, and validated reverse-phase high-performance liquid chromatography (HPLC) method for the determination of imatinib mesylate and its dimer impurity in pharmaceutical dosage form. Methods: A HPLC instrument incorporated with column HiQ Sil C18 (250 mm × 4.6 mm, 5 μm), mobile phase as methanol and acetate buffer pH 3.5 in the ratio of 80:20 v/v was used for the determination of the imatinib mesylate and its dimer impurity. The detection wavelength was set at 273 nm. The flow rate of the mobile phase was 1.0 mL/min. Results: The retention time for imatinib mesylate was 8.060, and for dimer impurity, it was 11.398. The calibration plot was linear (R2=0.9971) and the % mean recoveries for imatinib mesylate were in the range of 99.83–101.57, and for dimer impurity, it was in the range of 98.16–99.18. The limit of detection concentration was found to be 0.570 μg/ml for imatinib mesylate and 0.033 μg/ml dimer impurity and limit of quantification concentration was 1.728 μg/ml for imatinib mesylate and 0.099 μg/ml dimer impurity. Conclusion: The projected method was validated and successfully functional for the estimation of imatinib mesylate and dimer impurity in formulations. It can be adopted apparently for routine quality control and research tests.